Similarities and differences in the motivational basis of zoophraseological units (in Kazakh and Turkish languages) (Journal of Oriental Studies, 2021)
The article is dedicated to the phraseological units with zoonimic components in Kazakh and Turkish languages. The national-cultural specificity of the perception of the world by the Turkic peoples is manifested in zoo-phraseologiсal units. Despite the fact that zoonymic phraseological units in Kazakh and Turkish linguistics are comprehensively considered in the works of scientists from the semantic-structural, ethnolinguistic, cognitive points of view, today we consider it important to compare zoophraseological units between related languages in the context of the continuity of language and culture. Linguocultural semantics of Turkic zoophraseological units highlights the relationship between the language and the culture, linguocultural information about everyday life, customs and beliefs of Turkic people. The article identifies similarities and differences in the motivational basis of the phraseological units where animal names are used in the Turkic languages. The objective of the study is to analyse the semantic structure of zoophraseological units from a linguocultural point of view. First of all, the standard phraseological collocations associated with horses are summarized and explained with the help of phraseological dictionaries of the two languages, then the similarities and differences of Turkic people in the motivational basis of zoophraseological units are analyzed. The ethnic and cultural code typical for a particular nation is found under the zoophraseological units analysed in the course of the study. The study of the semantic and motivational basis of zoo-phraseological units in the Turkic languages is important in the vocabulary of the Turkic languages.Key words: zoonym, zoophraseological unit, zoonimic code, ethnocultural code.